Interactive Media Articulate Storyline to Improving Students’ Learning Outcomes on Traditional Engklek Games Material - Milenia, Rindita; Nurharini, Atip (Universitas Pendidikan Ganesha, 2023)
The application of traditional games in learning is still rarely implemented in elementary schools. Therefore we need learning media that is able to introduce traditional technology based on technology that is interesting for students. This study aims to analyze the effectiveness of interactive learning media Articulate Storyline in improving learning outcomes in fourth grade students Movement material on Traditional Engklek Games. The type of research used is research and development that refers to the ADDIE model. Determination of internal media validity is done by carrying out validation to experts and practitioners of media and material. Effectiveness is then determined by conducting small scale and large scale tests through pretest and posttest. The t-test results showed that the sig. value (2-tailed) is 0,000 meaning < 0.05. The N-Gain test shows a value of 0.69 with a medium category, so it can be concluded that there is an increase in the average value of the pretest and posttest. The conclusion of this study is that the interactive learning media Articulate Storyline is useful and effective used to improve the learning outcomes of fourth grade students on Movement on Traditional Engklek Games.